Une Transition périurbaine - Hervé Davodeau; Pierre Donadieu; André Fleury (Projets de Paysage)
This article raises the territorial transformation of the Anet canton (Eure-et-Loir) at the North end of the Eure-et-Loire and the Region Centre. This territory is subject to the increasing attraction of the big cities of the Bassin Parisien. This attraction comes from cities external to its territorial heritage : from Eure (Haute-Normandie) and mainly from Yvelines (Ile-de-France). Several indicators outline this process : intermunicipal reorganisation, inhabitant’s mobility, peri-urbanisation of burgs, villages, etc. The defence of the countryside is very active ; even if the agriculture has lost its economic links at a local level, its space is considered more and more as a Parisian countryside. The analysis is based essentially on the votes counting of the canton villages during the last thirty years and on several interviews conducted beyond several farmers. The Anet canton constitutes an illustration of the emergence of new « urban countrysides», of their territorial dynamics, and the challenges faced by the local actors.